DEVELOPING AN ENGLISH-SPEAKING SKILLS ASSESSMENT RUBRIC FOR AUTISM CHILDREN USING UNIVERSAL DESIGN FOR LEARNING - Solo, Lenny; Lustyantie, Ninuk; Murtadho, Fathiaty (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2025)
This study aims to develop an adaptive English-speaking skills assessment rubric for children with Autism Spectrum Disorder (ASD) using the principles of Universal Design for Learning (UDL) in a Special Education School (SLB). The need for an inclusive and flexible assessment tool that accommodates the diverse communication needs of children with ASD in language learning contexts, particularly English, is crucial. The research follows a systematic methodology consisting of needs analysis, rubric development, expert validation, pilot testing, revisions, and finalization. The rubric developed integrates UDL principles to ensure that assessments capture both verbal and non-verbal communication skills, such as gestures, visual aids, and assistive technologies. The findings from the expert validation process revealed that the rubric was clear, comprehensive, and adaptable to various student needs, providing a more holistic assessment of speaking skills. Teachers reported increased engagement and flexibility in using the rubric, which allowed students to express themselves in multiple ways. The pilot test indicated high inter-rater reliability (Cronbach’s alpha = 0.85) and demonstrated that the rubric effectively assessed students with varying levels of proficiency. Students who previously struggled with verbal communication showed improvement through the use of non-verbal means, enhancing their participation in the assessment. This study highlights the potential of integrating UDL principles into assessment rubrics to support the inclusive education of children with ASD and provide more accurate and equitable evaluations of their language skills.